Control of Plasmodium falciparum infection by human natural killer cells - Ye, Weijian (2017)
Natural killer (NK) cells are key components of the innate immune system, and play critical roles in the control of acute infection by malaria parasites. It is known that the secretion of IFN-γ by NK cells is a key determinant for disease resistance. However, much less is known about its cytotoxicity on infected red blood cells (iRBC). Also, how NK cells identify and respond to iRBC remains to be characterized. Here we show that control of parasitemia by NK cells was contact-dependent and involved cytolytic granules. Video microscopy demonstrated osmotic lysis of iRBC by NK cells. Furthermore, NK cells preferentially lysed trophozoites and schizont-stage iRBC, and such lysis required complex interactions of multiple activation signals provided by LFA-1, TLR2 and TLR4, as well as signaling through MYD88-dependent and TBK/IKKε-dependent pathways. Interestingly, NK cells from about 30% of malaria naïve donors do not eliminate iRBC, and upregulate the inhibitory NKG2A receptor instead of activation molecules, like CD69 and CD25. KIR genotyping further demonstrated increased frequencies of KIR2DS1 and KIR2DS2 in these donors. We further show that NK cell can control P. knowlesi parasitemia, demonstrating species-transcending immune control of this zoonotic parasite. In addition, over-expression of surface variant antigens by iRBC appeared to aid iRBC evasion from NK cell lysis. Together our study demonstrates the multifaceted interactions of NK cells and P. falciparum iRBC, and identifies the interplay of activation and inhibitory signals in the control of parasitemia by NK cells.